A semi-active toroidal TLCD for multidirectional vibration reduction of structures. (1st December 2022) - Zhang, Jian; Ding, Hao; Wang, Jin-Ting
Abstract: The toroidal tuned liquid column damper (TTLCD) is a recently developed device to mitigate multidirectional vibrations of structures. In this paper, a semi-active TTLCD (S-TTLCD), which can automatically identify the frequency change of structures and tune its natural frequency correctly by adjusting the liquid level, is proposed. The feasibility of the S-TTLCD is proved experimentally. The impacts of several important parameters, such as the multi-stage stiffness variation of structure, the pump flow rate, the mass ratio, and the damping ratio, on the performance of the S-TTLCD are evaluated numerically. The results confirm that the S-TTLCD is well adaptive and reduces the structural response more significantly when the structural natural frequency changes, compared to the passive TTLCD.